CAPITAL STRUCTURE IN EMERGING MARKETS: THE CASE OF SERBIAN JOINT-STOCK COMPANIES - Arsov, Sasho (Institut ekonomskih nauka, Beograd, 2016)
This paper is an attempt to extend the empirical research on the capital structure theory to a post-transition economy and to determine if there are any factors that could be linked to the behaviour of the companies with respect to their selection of the sources of financing. The study is based on a sample of joint-stock companies, most frequently traded on the Belgrade Stock Exchange, and using their financial data for a period of 6 years, it applies a panel regression model. The regression results show that the leverage of the analysed companies is positively related to their size and inversly related to the tangibility of their assets, profitability and the effective corporate tax rate. Surprisingly, no relation has been found between the level of fixed-asset investments and the use of debt. These results do not give sufficient support for any of the capital structure theories, but the closest match is some form of a modified pecking order.
Keywords: capital structure, leverage, financing, debt, equity, transition